If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 17 = -19 Reorder the terms: 17 + x = -19 Solving 17 + x = -19 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-17' to each side of the equation. 17 + -17 + x = -19 + -17 Combine like terms: 17 + -17 = 0 0 + x = -19 + -17 x = -19 + -17 Combine like terms: -19 + -17 = -36 x = -36 Simplifying x = -36
| 1536=6x^2 | | 225-7x=29x+21 | | 5a-20=-5+8a | | 2z^2+7z-15=0 | | (9-0.8x)(5-0.5x)=0 | | 9s^2+3s-20= | | 183-4x=23x+24 | | 14-8x=90-22x | | 7.6=y-5 | | 186-6x=6x+6 | | 7x-19.4=4x+10 | | -15-2=6x+6 | | X^2+x-182=0 | | (x)(x-5)=24 | | 2(1-3x)-2(4x-5)=-2 | | 112-4x=3x+14 | | 3x-(6x+2)=-3x+2 | | y^2+y-42= | | 4x-1=50+x | | 4x+13=-107-8x | | 2.7+0.3x=0.6 | | y^2+y-45= | | 2x-5=99 | | -12a=-3-13 | | 3.6x-25=1.4x+8 | | 2x-6=9x-41 | | -5(m+2)-m-7=-6(m+5)+13 | | 0.4x+0.1=-0.3 | | x-1=5.76 | | 5x+39=14x-69 | | (5x+4)*(2x^2-9x+9)=0 | | -2p+5=-15 |